Volcanoes - Furneaux, Rupert (Harmondsworth Puffin Books, 1974)
Discusses the characteristics of volcanoes, how they are born, erupt, and become dormant and describes some of the world's major volcanoes.
Keywords: Volcanoes -- Juvenile literature